The Influence of User-Generated Content and Electronic Word of Mouth (e-WOM) on TikTok on Gen Z Purchase Intentions toward Ella Skincare - Salma Talitha Ningrum; Kristina Anindita Hayuningtias (Golden Ratio of Mapping Idea and Literature Format, 2026)
The development of digital technology and the increasing use of social media among Generation Z has encouraged the use of marketing strategies based on User Generated Content (UGC). TikTok, as a popular social media platform, allows users to generate and share brand-related content, which then develops into Electronic Word of Mouth (e-WOM) through the process of interaction and information dissemination between users. The purpose of this study is to analyze how UGC and e-WOM contribute to increasing Generation Z's purchase intention for Ella Skincare products. This study uses a quantitative approach with a survey method of 160 Generation Z respondents who actively use TikTok and are familiar with Ella Skincare-related content. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that UGC does not have a significant effect on purchase intention, while e-WOM has a positive and significant effect on purchase intention. These findings confirm that user-generated content is not yet able to directly drive purchase intention. However, user reviews play an important role in shaping consumer perceptions and influencing Generation Z's purchase intention in the digital era. This study reinforces the application of the Stimulus–Organism–Response (S-O-R) model in the context of digital marketing and provides practical implications for marketers in designing effective UGC to encourage e-WOM and increase consumer purchase intention.